Program razvoja održivog turizma u Sisku i Petrinji - Koščak, Marko; Pavlakovič, Barbara; Padjen Đurić, Ingrid; Jurakić, Marko (2022)
The Development Program of Sustainable Tourism in Sisak-Moslavina County. The present book results from a project with which we wanted to stimulate sustainable tourism across Croatian Sisak-Moslavina County. Sisak-Moslavina County is located in Central Croatia, which has a favourable position between Slovenia, Bosnia and Herzegovina, and Serbia. With its natural resources, it has great potential for sustainable tourism development. As a cultural centre, Sisak enables the development of industrial and urban tourism, while Petrinja offers activities in nature and learning about heritage and tradition (such as pottery). A great attraction for tourists is also the nature of Lonjsko Polje Park. Tutors and 1st-year students of the Master’s program at the Faculty of Tourism University of Maribor addressed the strategic challenge of tourism development together through participatory planning and local community involvement. After analysing the situation, they prepared a development vision, identified the priority work areas, and defined the indicators and ways they would be monitored. The action plan itself is based on the theory of sustainable tourism development in protected areas, presented at the beginning of this book.
Keywords: development programme; sustainable development; rural tourism; urban turism; restauration of tourist infrastructure; Sisak-Moslavina Country